A Review of the Application of Covalent Organic Frameworks in Uranium Extraction from Seawater - Guo, Minghao; Wang, Yibo; Li, Meiyi; Tian, Jiazheng (International Journal of Materials Science and Technology Studies, 2026)
The ocean contains abundant uranium resources. From the perspectives of resource utilization and ecological environmental protection, uranium extraction from seawater represents a highly promising method for uranium resource regeneration. This approach holds significant potential for the advancement of nuclear power and the broader application of reliable energy. Covalent organic frameworks (COFs) are ideal materials for extracting U(VI) ions from seawater due to their inherent porosity, robust skeletal structure, chemical stability, and good structural regularity. This paper reviews recent progress in the efficient preconcentration and separation of U(VI) from seawater through adsorption and photocatalysis. The current developments and potential of U(VI) extraction using functional COFs are also discussed. Lastly, this review highlights the opportunities and challenges associated with COF-based seawater uranium extraction, offering insights into its future development prospects. This work aims to deepen readers’ understanding of the key technologies involved in COFs for seawater uranium extraction, and to identify more efficient and environmentally friendly COF-based materials, thereby supporting the growth of the nuclear power industry.